Assessing Anti-Bullying Program Implementation in Early Childhood Education: A CIPP-Based Evaluation Study - Hanifah, Inas; Muthmainah (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
This study evaluates the implementation of an anti-bullying program at TK Sekolahku My School Sleman using the CIPP (Context, Input, Process, Product) evaluation model to create a safe and inclusive learning environment for students. A qualitative approach was employed, utilizing interviews, observations, and document analysis to gather in-depth data on the program's context, supporting inputs, implementation processes, and resulting outcomes. The findings indicate that the program was systematically designed and implemented by the school's environmental needs. Context evaluation reveals that the program was developed based on child protection policies adapted from international models and tailored to the school’s culture. Regarding input, educators demonstrated competence in handling bullying cases, although the term bullying was not explicitly used in classroom instruction. Process evaluation shows that the program was integrated into students' daily routines through habituation, storytelling methods, and reinforcement of rules and consequences. Product evaluation finds that the program successfully instilled values of empathy and courage in students, as evidenced by their ability to reject inappropriate behavior and heightened social awareness. However, this study is limited by its population scope and restricted access to internal documents, which may affect the generalizability of the findings. Future research is recommended to expand participant coverage and develop more structured measurement instruments to quantitatively assess changes in student behavior. The study highlights the importance of strengthening anti-bullying programs by involving parents and conducting periodic evaluations based on measurable indicators to enhance program effectiveness in early childhood education.